Diagnóstico do serviço de abastecimento de água segundo a percepção do usuário em Tibau-RN - Aquino, Victor (Universidade Federal Rural do Semi-Árido, 2018)
The present work had as objective to measure the quality of the water service in the city of Tibau-RN, by means of research of data of users, and to describe the model used in the city for the water supply. The research was carried out in the field and in a documentary form, with the use of data from the service made by the Water and Sewer Company of Rio Grande do Norte (CAERN). The choice of residences, where the questionnaires were applied, was performed in a random manner, and the data were submitted to a descriptive statistical analysis. Water polling station, which was considered adequate by CAERN users.
Monografia
Keywords: Abastecimento de água; Satisfação dos usuários; CAERN; Water supply; User satisfaction; CAERN; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA